Sulphur and chlorine content in forages from defined region - Marija RAJČEVIČ; Anton ILC; Peter KUMP; Marijan NEČEMER (Acta Agriculturae Slovenica, 2000)
In 1999 5 samples of pasture grass, 13 samples of grass silage, 6 samples of hay and 7 samples of maize silage were taken at random. All samples were from the defined region, and the forage was produced in similar soil and weather conditions. The grass botanical composition was comparable as well. The pasture and grasslands were manured by pig and bovine slurry. The content of sulphur and chlorine was determined by roentgen fluorescent analysis. Grass dry matter contained 2.56 ± 0.70 g of sulphur (CV = 27.29%) and 9.15 ± 4.18 g of chlorine (CV = 45.49%), grass silage 2.38 ± 0.49 g of sulphur (CV = 20.67%) and 7.19 ± 1.89 of chlorine (CV = 26.34%), hay 1.93 ± 0.48 g of sulphur (CV = 24.84%) and 5.72 ± 1.98 of chlorine (CV = 34.68%), and maize silage contained 0.88 ± 0.25 g of sulphur (CV = 28.14%) and 1.98 ± 0.86 g of chlorine (CV = 43.39%). Some results for sulphur as well as for chlorine deviated a great deal from the mean value and median. More attention should be paid to collection and preparation of samples for the analysis and determination of ash insoluble in hydrochloric acid.